THE EFFECT OF SPIRITUAL INTELLIGENCE (SQ) AND PERSONALITY TYPES ON AUDITOR’S ABILITY TO DETECT FRAUD - Romy Andriyanto; Effriyanti Effriyanti; Angga Hidayat (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2018)
Nowadays, the recruitment of an auditor is still based on the intellectualintelligence to assess whether a person is eligible to be an auditor or not. The purpose of this study is to recognize the effect of spiritual intelligence and personality types on auditor ability to detect fraud at public accountant office in South Jakarta. The population of the study are the auditors who work in Public Accounting Firm in South Jakarta. The sample selection is conducted by convenience sampling method. There are 8 Public Accounting Firms in South Jakarta area which fulfill the criteria as research sample, then the questionnaires distributed are 85 data. However, the questionnaires that meet the criteria are 75 data. Consequently, those 75 data can be further processed by using multiple linear regression. The results of the study indicate that: (1) Spiritual Intelligence (SQ) has a significant effect on the ability of Auditors in Detecting fraud with Sig. 0.000 (0,000 <0,05), (2) Personality Type has no significant effect on Auditor'sAbility in Detecting fraud with sig value. 0,654 (0,654> 0,05), and SpiritualIntelligence (SQ) and Personality Type simultaneously have a significant effect on Auditor's Ability to Detect fraud with the sig value. 0.000 (0,000 <0.05).